An examination of performance management in public health care in the Emirate of Dubai - AL MAMARI, SHAIKHA ABDULLAH SALIM (2017)
The study investigates the prevailing performance standards , modes of performance measurements, and the resulting ambiguities in performance measurement. In view of the public sector health care facilities and initiatives of the Dubai government to provide quality health services, the performance of employees need to be aligned with the objectives of healthcare services. This research employs a descriptive methodology design and a survey of 150 employees of health care centres in Dubai was undertaken. The data analysis was conducted through statistical measures of descriptive and inferential statistics. The findings of the data analysis revealed that performance management system attributes are highly correlated with costs incurred in measurement, processes, time required, and the value concepts of the healthcare management. On the other hand, correlation with factors in the external environment and quality of performance management systems (PMS) are found very low and insignificant. The recommendations included more proactive adherence to changes in external environment and greater focus on the quality of performance measurement and management systems. The study has certain limitations in its dependence on a single data collection method - the quantitative method - and the restricted sample size from public health care centres of Dubai only.